Immune Modulation in HLA-G Expressing Head and Neck Squamous Cell Carcinoma in Relation to Human Papilloma Virus Positivity: A Study From Northeast India - Sarmah, Neelanjana; Baruah, Munindra Narayan; Baruah, Shashi (Frontiers in Oncology, 2019)
Background: Tumor specific ectopic expression of the immunomodulatory molecule, HLA-G is known to mediate immune tolerance and promote carcinogenesis. Viruses too employ strategies to evade immune surveillance. Considering the role of both HLA-G and HPV in tumor growth and progression, it is pertinent to investigate the relationship between HLA-G and HPV in context of immune modulation in HNSCC. Method: A hospital based case – control study was conducted in histopathologically confirmed HNSCC tissues. HLA-G isoform expression and HPV association studies were carried out and mRNA levels of HLA-G, markers of proliferation and differentiation (ki-67, keratin 18, cyclin D1), immune checkpoint molecules (IL-10, PD-1. TGF-β), SOCS (SOCS1 and SOCS3) and pro-inflammatory cytokine IFN-γ were determined. Results: Higher expression of HLA-G was noted in HPV positive tumors (5.14 fold, p=0.002). HLA-G7 was the most frequent isoform (29/80) found in HNSCC particularly in HPV positive tumors (13/16). In HPV negative tumors, all the checkpoint molecules were upregulated along with pro–inflammatory IFN-γ. In contrast, in HPV positive tumors, IFN-γ expression was higher (2.12 fold) but levels of IL-10, PD-1, TGF-β, SOCS1 and SOCS3 were markedly lower (fold change of IL-10 = 0.37, PD1 = 0.41 and TGF-β = 0.17, SOCS1 = 0.055, SOCS3 = 0.027). HPV positive tumors were more proliferative and differentiated with higher expression of ki-67 and keratin18 (6.25 fold, p=0.079 and 10.62 fold, p=0.009). Decreased expression of cyclin D1 was noted in HPV positive tumors (6.94 fold, p=0.006) than HPV negative tumors (17.69 fold). Also, HLA-G7 expressing HPV positive tumors showed lowest expression of cyclin D1. Interestingly, SOCS showed normal expression in HLA-G7 expressing HPV negative tumors (1.2 and 1.4 fold). IFN-γ was downregulated in HPV positive tumors without HLA-G7 (0.31 fold). Conclusion: Our data suggests that SOCS were downregulated irrespective of HLA-G positivity and IFN- γ expression was appeared to be mediated by HLA-G. SOCS are reported to have anti-tumor activity and also SOCS and soluble HLA-G are known to interfere with cell cycle progression. Hence, through regulating HLA-G expression, HPV positive tumors could mediate immune suppression by manipulating SOCS, IFN-γ, IL-10 and cyclin D1 pathways which needs further exploration.